2016
DOI: 10.20960/nh.98
|View full text |Cite
|
Sign up to set email alerts
|

Asociación entre el estado nutricional y la prevalencia de pie plano en niños chilenos de 6 a 10 años de edad

Abstract: entre el estado nutricional y la prevalencia de pie plano en niños chilenos de 6 a 10 años de edad. Nutr Hosp 2016;33:249-254 AbstractIntroduction: Given the increment of overweight and obese children, it is relevant to study not only metabolic but also musculoskeletal consequences that may affect motor functionality such as flat foot in this population. Objetive: To identify the association between nutritional status and the prevalence of flat foot in Chilean children from 6 to10 years old. Methods: Z-score … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Conversely, flat feet were found in 11% of the subjects [24]. A similar incidence of flat feet was observed in Chilean studies [25]. On the other hand, flat feet occurred in Bulgarian children in every fourth child, which is consistent with our research [21].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Conversely, flat feet were found in 11% of the subjects [24]. A similar incidence of flat feet was observed in Chilean studies [25]. On the other hand, flat feet occurred in Bulgarian children in every fourth child, which is consistent with our research [21].…”
Section: Discussionsupporting
confidence: 92%
“…The most common postural deviations in obese children and adolescents were valgus knees and flat feet [36]. A higher incidence of flat feet was also found in obese Chilean children in comparison to children with overweight and normal weight [25]. Purenovic reviewed international studies on postural defects, which, despite methodological differences, showed the negative impact of obesity on posture in children, even though it was not the most significant and basic risk factor [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All studies used BMI as OW/OB indicator, whereas three studies additionally reported fat mass composition [18][19][20] , two reported muscle mass composition 18,20 , two reported waist circumference 21,22 and one reported height-waist circumference 23 . BMI was always used to measure the obesity degree, and a wide range of cut-off points were identified: 22 studies used the Extended International (IOTF) cut-offs , seven the 90 th and 97 th percentiles (OW and OB respectively) [45][46][47][48][49][50][51] , seven cut-off points from their countries (Czech Republic, Mexico, Poland, Taiwan and USA) 18,[52][53][54][55][56][57] , six the World Health Organization cut-offs [58][59][60][61][62][63] , six the Centers for Disease Control and Prevention cut-offs [64][65][66][67][68][69] , one the National Institute of Health cut-offs 70 , and one did not report it 71 . Regarding postural alterations, four articles studied forward head [72][73][74][75] , five rounded shoulder 18,19,72,…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…BMI was always used to measure the obesity degree, and a wide range of cut-off points were identified: 22 studies used the Extended International (IOTF) cut-offs , seven the 90 th and 97 th percentiles (OW and OB respectively) [45][46][47][48][49][50][51] , seven cut-off points from their countries (Czech Republic, Mexico, Poland, Taiwan and USA) 18,[52][53][54][55][56][57] , six the World Health Organization cut-offs [58][59][60][61][62][63] , six the Centers for Disease Control and Prevention cut-offs [64][65][66][67][68][69] , one the National Institute of Health cut-offs 70 , and one did not report it 71 . Regarding postural alterations, four articles studied forward head [72][73][74][75] , five rounded shoulder 18,19,72,73,76 , 12 thoracic hyperkyphosis 10,18,23,34,59,70,72,74,75,77-79 , 14 lumbar hyperlordosis 18,20,23,34,48,59,72,74,<...>…”
Section: Sample Characteristicsmentioning
confidence: 99%